Turn the Beat Around: A Stroke Prevention Program for African‐American Churches. Issue 1 (25th September 2015) - Williams, Lovoria B.; Franklin, Brandi; Evans, Mary B.; Jackson, Chazeman; Hill, Alethea; Minor, Michael
Abstract: Objective: The objective was to pilot a socioculturally tailored church‐based stroke prevention program delivered by trained community health workers (CHWs) and to test its effects on participant knowledge scores. Design and Sample: A single‐group, pre‐post test pilot study was conducted with a convenience sample of 201 adult African‐Americans recruited from nine churches in three Alabama counties. Measurements included participant weight, blood pressure (BP), physical activity level; knowledge related to hypertension, heart disease, and stroke; cigarette smoking; and access to care, as well as the Stages of Change constructs within the Transtheoretical Model. The intervention was a six‐session group‐based health education program delivered by trained CHWs. Measures: Measurements included participant weight, blood pressure (BP), physical activity level; knowledge related to hypertension, heart disease, and stroke; cigarette smoking; and access to care, as well as the Stages of Change constructs within the Transtheoretical Model. The intervention was a six‐session group‐based health education program delivered by trained CHWs. Results: From baseline to 12 weeks, knowledge increased significantly ( p < .001). Systolic BP measures improved ( p = .0008). More than half of participants lost weight; however, weight change did not reach significance ( p = .1380). Most (87%) participants indicated having a medical home at baseline; at the end of the study the percentage increased to 92% ( p = .0138). Conclusion: A church‐based intervention delivered by trained CHWs is feasible and may be a promising public health strategy to increase knowledge regarding hypertension and stroke prevention among African‐Americans.